RF parameters characterization of a flexible Cu-PDMS-Cu patch antenna - Mohd Ramly, Athirah; Abdul Malek, Norun; Ibrahim, Siti Noorjannah; Zainuddin, Ahmad Anwar (Praise Worthy Prize, 2017)
This paper presents a newly developed flexible Polydimethylsiloxane (PDMS)-Copper (CU) patch antenna. The circular-shaped antenna consists of a 21.28mm radial size Cu patch embedded on a PDMS square substrate. PDMS has a low loss tangent of 0.004 and a relative permittivity of 2.74 that will enhance the RF parameters of the flexible antenna. There are three layers of material used to build the antenna. The first and the third layers are made from Cu tape and function as the ground and patch respectively. Meanwhile, the sandwiched layer is the PDMS substrate. However, several limitations of the antenna were observed, including low adhesiveness between layers, which made it impossible to perform metal and dielectric depositions. Thus, a thin layer of PDMS has been built on top of a patch layer to increase the adhesive strength between the copper patch and the PDMS substrate. The paper also discussed the return loss of the antenna with and without sandwich in planar, bending in x-axis and y-axis. The measurements using a vector network analyzer (VNA) demonstrated that the sandwich antenna can resonate at 2.33GHz with a low return loss of 42dB. The work is a proof of the principle that the PDMS substrate can be proposed as a good substrate for antenna in conformal applications.